Narrating Displacement: Chinese-Indonesian Collective Memory in Lvdao Sanwen Ji (绿岛散文集 ) - Vasantadjaja, Livia (Lingua Cultura, 2025)
While ethnic Chinese-Indonesians are often stereotyped as ‘economic figures’, many are also actively engaged in literature. Among their literary contributions is The Green Island Prose Compilation (2015), which is a post-Reformasi anthology of Mandarin language prose selected from the monthly Lüdao column in the International Daily News. These writings reflect personal experiences and preserve the memory of ethnic Chinese life in Indonesia. This study aims to examine how individual life narratives in the Green Island Prose Collection, shaped by social and historical context, contribute to the collective memory of Chinese-Indonesians. It explores how literature serves as a medium for documenting everyday life, preserving cultural identity, and bridging generational gaps. This research employs a descriptive qualitative method, utilizes purposive sampling to identify relevant themes of prose, and applies content analysis based on Maurice Halbwachs’ theory of collective memory. The data includes prose works that reveal recurring themes such as childhood, family, social life, and historical events. The findings indicate that the collective memory among Chinese-Indonesians is constructed from individual memories, incorporating elements of childhood, adulthood, and historical recollections. This becomes a significant shared experience and memory repository. This study not only addresses a gap in the study of the Chinese-Indonesian literature but also provides insights into the role of literature in preserving culture, shaping identity, and facilitating intergenerational communication. In this way, it enhances the understanding of the Chinese-Indonesian community within the broader context of contemporary Indonesian society.